48. Local Implementation of an Antibiotic Stewardship Intervention for Asymptomatic Bacteriuria Through Centralized Facilitation Required Minimal Costs and Effort. (4th December 2021) - Rajan, Suja S; Grigoryan, Larissa; Van, John; Lichtenberger, Paola; Patel, Payal K; Shukla, Bhavarth; Calub, Feliza; Brown, Nui G; Nguyen, Phuong Khanh; Hershey, Cheryl; Drekonja, Dimitri M; Graber, Christopher J; et al.
Abstract: Background: The cost of an antibiotic stewardship intervention is an important yet often neglected factor in antibiotic stewardship research. We studied the costs associated with successful implementation of the "Kicking CAUTI" intervention to decrease treatment of asymptomatic bacteriuria (ASB). Methods: A central coordinating site facilitated roll-out of an audit and feedback intervention to decrease unnecessary urine cultures and antibiotic treatment in patients with ASB in four Veterans Affairs medical centers. Each site had a physician site champion, a part-time research coordinator, and 1-2 additional participants (often pharmacists). Participants kept weekly time-logs to collect the minutes associated with intervention tasks, and percent full-time effort (FTE) and costs were computed. For weeks with missing logs the average minutes for each activity associated with each type of professional was imputed. Salary information was obtained from the Bureau of Labor Statistics and Association of American Medical Colleges. Results: Research coordinator time comprised of majority of the personnel time, followed by the physician site champions (Figure 1). Each intervention site required about 10% FTE/year of a research coordinator, and 3.5% FTE/year and 3.8% FTE/year of a physician and pharmacist respectively. The coordinating site required 37% FTE/year of a research coordinator, and 9% FTE of a physician to spearhead the intervention. Research coordinators predominantly spent their time on chart-reviews and project coordination. Physician champions predominantly spent their time on delivering audit and feedback and project coordination. The intervention cost USD 22, 299/year per site on average, and USD 45, 359/year for the coordinating site. Conclusion: The Kicking CAUTI intervention was successful at reducing urine cultures and associated antibiotic use, with minimal time from the local team members. The research coordinators' time was primarily spent on collection of research data, which will not be necessary outside of a research project. Our model of centralized facilitation makes economic sense for widespread scale-up and dissemination of antibiotic stewardship interventions in integrated healthcare systems. Disclosures: Barbara Trautner, MD, PhD, Genentech (Consultant, Scientific Research Study Investigator)